Die vergleichenden linguistischen Untersuchungen im Bereich der Sportsprache – Methoden und Tendenzen - Jakub Dzidek (Linguistische Treffen in Wrocław)
The review article discusses the book ‘Language and Football’ by Eva Lavric and Gerhard Pišek (ed.), published in 2024. The introductory section addresses the role of sport, the value of which has increased over time. It has been an important part of shaping society with its currencies since ancient times. Language plays an extremely important role in sporting society because communication takes place within and through sport. However, sports language is constantly regarded as an undiscovered and complex phenomenon. As a result, any research in its field helps to clarify the phenomenon. Due to the lack of inter- and interlingual comparative research, any opportunity to highlight it is more valuable than gold. Consequently, the next part of the paper will highlight the articles in the volume that present comparative inter- and intralingual research at different levels. Above all, they look for the differences and similarities within the framework of the languages or language variants analysed. In the concluding section, brief evaluations and recommendations are suggested after reading the work.